History of Edu-Tourism for Strengthening Nationalism and Heroism in the City of Surabaya - Rojil Nugroho Bayu Aji,; Eko Satriya Hermawan,; Riyadi,; Agus Trilaksana,; Esa Patridina,; Nasution,; Moch. Mubarok Muharam,; Wisnu, (Technium Social Sciences Journal, 2023)
Surabaya is a big city in Indonesia and is known as the city of heroes. Surabaya received the title of city of heroes because of the struggle to defend Indonesia's independence from colonialism, especially during the November 10, 1945 War. The history of this city of heroes must always be so that it can be inherited by future generations as a historical insight that has significant value. Surabaya is rich with historical sites that can be used as examples and take lessons from the historical approach that exists and is attached to the site itself. Modeling in this historical approach can be done through history edu-tourism. This study uses the ADDIE research and development method. The product designed in this research is history edu-tourism. Through tourism, the important historical values ​​of the city of Surabaya can be transformed to the general public, either directly or indirectly in the context of strengthening nationalism. For example, in Surabaya there is the Bung Karno Birth House, the HOS Tjokroaminoto Boarding House, the Museum and the Tomb of dr. Soetomo, Museum W.R. Soepratman and the Tugu Pahlawan Surabaya Museum which can be used as a series of history edu-tourism.